A SYSTEMATIC REVIEW OF THE GENRE-BASED APPROACH IMPLEMENTATION TO IMPROVE EFL STUDENTS’ WRITING SKILLS - Aulia, Vivi (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
The genre-based approach (GBA) was one of the writing approaches that helps and facilitates students to explore a focused piece of writing. When students were required to create such a writing form, most of them tended to have difficulties in constructing structured writing. The GBA approach allowed students to improve their writing skills by following specific steps. This systematic literature review reviewed research articles discussing the improvements made in students’ writing outcomes by implementing the GBA. Fifteen research articles from nine different countries were selected from the ERIC, Google Scholars, and Semantic Scholars online article databases. They were analyzed to determine improvements in students’ writing skills based on the results of the research in these nine countries. The results showed that students investigated from research articles in the nine countries showed three types of improvement in writing: writing performance, writing achievement, and writing attitude. Specifically, 8 of 15 research results show that the implementation of GBA provides benefits to improve writing performance. Meanwhile, 5 of 15 research results mention that the students’ writing achievement in terms of their writing score is much better after implementing the GBA. Finally, two research showed an improvement in their writing attitude after the GBA implementation. The conclusion of this research indicates that the utilization of GBA can help and facilitate students to be more productive as well as improve their writing